The Triad of Progress: Science, Philosophy, and Economics in Sustainable Development - T. Karthikeyan; E. Vijay (International Journal of Land, 2024)
Sustainable Development Goals (SDGs) demand an integrated approach that transcends disciplinary boundaries. Science provides technological innovations and empirical insights, philosophy offers ethical foundations and critical reflections, while economics structures incentives and resource allocation mechanisms. This paper explores the interdependence of these three domains in shaping sustainable development strategies. By analyzing historical precedents, theoretical intersections, and contemporary case studies, we illustrate how a synergistic approach can bridge gaps in policy implementation. The study highlights the role of ethical economic models, scientific breakthroughs, and philosophical frameworks in addressing challenges such as climate change, social inequality, and responsible consumption. Furthermore, we argue that sustainability requires a balance between economic growth and environmental stewardship, underpinned by ethical considerations and scientific advancements. The paper concludes with recommendations for policymakers, researchers, and practitioners to foster interdisciplinary collaboration and implement holistic sustainability strategies. This triadic perspective offers a robust framework for achieving SDGs and ensuring long-term global resilience.
Keywords: Economics; Interdisciplinary Approach; Science; philosophy; sustainable development